Antimicrobial cellulose paper tuned with chitosan fibers for high-flux oil/water separation. (15th July 2023) - Ling, Hao; Wang, Lei; Lin, Qixuan; Huang, Quanbo; Zhang, Xiaoqian; Ren, Junli; Li, Ning; Zhou, Cheng; Lin, Zhiwei; Zhou, Jingpeng; Wei, Wenguang; Wang, Xiaohui
Abstract: Separating films with both high efficiency and large flux are desperately needed to meet the rising demand for the treatment of oily wastewater, while traditional oil/water separation papers with high separation efficiency usually suffered from low flux due to the unsuitable size of filtration pores. Herein, we report a bio-based porous, superhydrophobic, and antimicrobial hybrid cellulose paper with tunable porous structures for high flux oil/water separation. The size of pores in the hybrid paper can be tuned by both physical supports provided by the chitosan fibers and the chemical shielding supplied by the hydrophobic modification. The hybrid paper with increased porosity (20.73 μm; 35.15 %) and excellent antibacterial properties can efficiently separate a wide range of oil/water mixtures, solely by gravity, with outstanding flux (maximum of 23, 692.69 L m −2  h −1 ), tiny oil interception, and high efficiency of over 99 %. This work provides new sights in the development of durable and low-cost functional papers for rapid and efficient oil/water separation.